Randomized Open Controlled Clinical Trial to Evaluate the Effect of Patol Shunthi Ghruth in Urdhwag Amlapitta - Radhika, Sahu Hrishikesh; Dipali, Swami (International Research Journal of Ayurveda & Yoga, 2022)
Amlapitta is a life-style related disease prevalent all over the world. Amlapitta is disorder caused by habitat, irregular diet schedule and activities but also as a result of Psychological and physiological observation. Amlapitta is a common functional disease of Annavaha srotas. Materialistic life style provokes people to run behind a busy, stressful life which is least concern towards proper food habits. As the life is becoming very fast and the rate of urbanisation is growing. Adhyashana (eating after meal), Vishamashana (diet on irregular time and quantity), and wrong behavioural patterns such as Vegadharana (suppression of urges) leads to vitiation of Doshas. Pitta has been vitiated, junk food and drink that are incompatible, spoiled, and very sour and that is capable of causing vitiation of pitta and increase drava and amla guna of pitta.